C04 FAN1 controls cag repeat expansion in Huntington's disease by dual functions, MLH1 retention and nuclease activity. (12th September 2022) - Goold, Robert; Hamilton, Joseph; Menneteau, Thomas; Flower, Michael; Bunting, Emma; Aldous, Sarah; Porro, Antonio; Vicente, José; Allen, Nicholas; Wilkinson, Hilary; Bates, Gillian; Sartori, Alessandro; et al.
Abstract : Background: Human genetic data has revealed that, aside from inherited CAG repeat length, DNA repair maintenance is the main factor governing Huntington's disease (HD) age at onset. Genetic modifiers in the DNA repair network operate via somatic expansion – a process whereby the HTT exon 1 CAG repeat tract expands throughout a patient's lifetime – and includes the nuclease FAN1 and several mismatch repair (MMR) factors, such as MSH3 and MLH1. Aims: FAN1 has previously shown to suppress somatic expansion, however, we intended to clarify the mechanism behind this observation. Methods: We expressed GFP-tagged FAN1 variants and longitudinally measured somatic expansion of an exogenous 118CAG exon 1 construct via fragment analysis, while also examining the DNA repair interactome by co-immunoprecipitation. Functional assays were used to monitor the effect of these FAN1 variants on DNA repair pathways. Results: We demonstrated that FAN1 directly competes with MSH3 for MLH1 through an evolutionary conserved N-terminal domain, 126SPYF129. Mutation of this motif in full-length FAN1 increased the rate of CAG repeat expansion and negated MLH1-binding, indicating the two phenomena are mechanistically linked. Furthermore, preventing formation of the FAN1-MLH1 complex increased mismatch repair activity and increased recruitment of MLH1 to the HTT CAG repeat tract. By nullifying the nuclease activity of FAN1, through the D960A mutation, we observed that MLH1-binding and nuclease activity account for the entirety of FAN1's protective influence on somatic expansion. Conclusions: Therefore, FAN1 can suppress somatic expansion by sequestering MLH1, therefore regulate the mismatch repair pathway, and involves nuclease activity.